Monitoring of aflatoxin M1 in raw cow milk in Croatia during winter 2015 - Nina Bilandžić; Ivana Varenina; Božica Solomun Kolanović; Đurđica Božić Luburić; Miroslav Benić; Luka Cvetnić; Sanin Tanković; Željko Cvetnić (Mljekarstvo)
A total of 548 raw milk samples were collected in the western, central and eastern regions of Croatia during February and March 2015. Aflatoxin M1 (AFM1) concentrations were quantified by the enzyme immunoassay method. The method limits of detection (LOD) and quantification (LOQ) were 22.2 and 34.2 ng/kg, respectively. The mean AFM1 levels measured in the three regions were (ng/kg) as follows: western 3.69, central 3.11 and eastern 4.14. In total, the 548 samples analysed concentrations were below the LOD value and accordingly below the European Union maximum residue level (EU MRL) of 50 ng/kg. The results suggest an absence of use of contaminated with aflatoxin B1 supplementary feedstuff for lactating cows in winter 2015. Such results might be related to the improved storage conditions for feed as well as to the enhanced and more stringent feed control system for mycotoxins in Croatia.